2018
DOI: 10.21608/jfds.2018.36087
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Egyptian Moringa oleifera Lipids (Whole Seeds and Kernels)

Abstract: Moringa seeds (Moringa oleifera) are rich in oil contents, the purpose of this study is to extract the oil from the whole seeds and kernels of the Egyptian Moringa by cold and hot extraction methods and to study the effect of extraction method on the composition of fatty acids, tocopherols and triglycerides in extracted oil. The results indicated that the amount of extracted oil by hot extraction were 28.85% and 39.23% and by cold extraction were 21.39% and 29.34% for whole seeds and kernels, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…aand g-tocopherols were the highest tocopherols in MSO and CSO and the values were within the ranges reported by others (Taoufik et al, 2015;Gharby et al, 2015;Al-Juhaimi et al, 2017;Salama et al, 2018). aand g-tocopherols in MSO and CSO and their blends during storage for four weeks at 50°C were presented in Tables 6 and 7.…”
Section: The Change In Tocopherolssupporting
confidence: 86%
“…aand g-tocopherols were the highest tocopherols in MSO and CSO and the values were within the ranges reported by others (Taoufik et al, 2015;Gharby et al, 2015;Al-Juhaimi et al, 2017;Salama et al, 2018). aand g-tocopherols in MSO and CSO and their blends during storage for four weeks at 50°C were presented in Tables 6 and 7.…”
Section: The Change In Tocopherolssupporting
confidence: 86%
“…Among these TAGs, the glycerol trioleate (OOO) was the most abundant (32.42±0.12%) followed in descending order by the glyc-erol palmitate-dioleate (POO) , the glycerol stearate-dioleate (SOO) , and the glycerol stearate-linoleate-oleate (SLO) with respective values of 14.12±0.06%, 11.97±0.05%, and 9.72±0.02%. The predominance of the glycerol trioleate, the glycerol palmitate-dioleate (POO) , and the glycerol stearate-dioleate (SOO) is in accordance with previous studies conducted by Abdulkarim et al 7) and Salama et al 23) on Malysian and Egyptian MoSO extracted by petroleum ether, respectively. In fact, the latter found that trioleate (OOO) was the predominant TAG with a content varying between 33.75% and 36.70%.…”
Section: Triacylglycerol Compositionsupporting
confidence: 91%
“…Currently, while we are aware that several have already attempted to characterise MOSO (Tsaknis et al ., 1999; Anwar & Bhanger, 2003; Abdulkarim et al ., 2005; Salama et al ., 2018); a full literature search shows that there is almost no additional TAG information since Abdulkarim et al . (2005), who studied the characterisation of MOSO and found 13.9% of unidentified TAG using an HPLC instrument with detector RID.…”
Section: Introductionmentioning
confidence: 99%
“…Salama et al . (2018) used gas chromatography to characterise the TAG of Egyptian MOSO lipids, using gas chromatography to show the relative percentage of TAG peaks and TAG ID determination but found unidentified TAG data approximately 14.12–15.93%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation